Alleviating managerial dilemmas in human‐capital‐intensive firms through incentives: Evidence from M&A legal advisors - Chatain, Olivier; Meyer‐Doyle, Philipp (Strategic Management Journal, 2017)
Research summary: We examine how human‐capital‐intensive firms deploy their human assets and how firm‐specific human capital interacts with incentives to influence this deployment. Our empirical context is the UK M&A legal market, where micro‐data enable us to observe the allocation of lawyers to M&A mandates under different incentive regimes. We find that law firms actively equalize the workload among their lawyers to seek efficiency gains, while “stretching” lawyers with high firm‐specific capital to a greater extent. However, lawyers with high firm‐specific capital also appear to influence the staffing process in their favor, leading to unbalanced allocations and less sharing of projects and clients. Paradoxically, law firms may adopt a seniority‐based rent‐sharing system that weakens individual incentives to mitigate the impact of incentive conflicts on resource deployment . Managerial summary: The study highlights the dilemmas when professional service firms allocate their key individuals to incoming projects, and the role that monetary incentives play in aggravating or alleviating these dilemmas. In the context of UK M&A law firms, we find that partners have a tendency to be attached to too many projects and not to share enough work, which is exacerbated when individual monetary incentives are stronger. Firms adopting a seniority based incentive system (lockstep system) are able to alleviate this effect. This implies that there is a trade‐off between rewarding personal performance versus balancing workloads and fostering collaboration among professionals . Copyright © 2015 John Wiley & Sons, Ltd.